Stability regions around the components of the triple system 2001 SN263 - Araujo, R. A. N. [UNESP]; Winter, O. C. [UNESP]; Prado, A. F. B. A.; Sukhanov, A. (Wiley-Blackwell, 2012)
Space missions are an excellent way to increase our knowledge of asteroids. Near-Earth asteroids (NEAs) are good targets for such missions, as they periodically approach the orbit of the Earth. Thus, an increasing number of missions to NEAs are being planned worldwide. Recently, NEA (153591) 2001 SN263 was chosen as the target of the ASTER MISSION the First Brazilian Deep Space Mission, with launch planned for 2015. NEA (153591) 2001 SN263 was discovered in 2001. In 2008 February, radio astronomers from Arecibo-Puerto Rico concluded that (153591) 2001 SN263 is actually a triple system. The announcement of ASTER MISSION has motivated the development of the present work, whose goal is to characterize regions of stability and instability of the triple system (153591) 2001 SN263. Understanding and characterizing the stability of such a system is an important component in the design of the mission aiming to explore it. The method adopted consisted of dividing the region around the system into four distinct regions (three of them internal to the system and one external). We performed numerical integrations of systems composed of seven bodies, namely the Sun, Earth, Mars, Jupiter and the three components of the asteroid system (Alpha, the most massive body; Beta the second most massive body; and Gamma, the least massive body), and of thousands of particles randomly distributed within the demarcated regions, for the planar and inclined prograde cases. The results are displayed as diagrams of semi-major axis versus eccentricity that show the percentage of particles that survive for each set of initial conditions. The regions where 100 per cent of the particles survive are defined as stable regions. We found that the stable regions are in the neighbourhood of Alpha and Beta, and in the external region. Resonant motion of the particles with Beta and Gamma was identified in the internal regions, leading to instability. For particles with I > 45 degrees in the internal region, where I is the inclination with respect to Alphas equator, there is no stable region, except for particles placed very close to Alpha. The stability in the external region is not affected by the variation of inclination. We also present a discussion of the long-term stability in the internal region, for the planar and circular case, with comparisons with the short-term stability.
Keywords: methods: N-body simulations; celestial mechanics; minor planets, asteroids